PENGARUH MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN APLIKASI CANVA TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS IV SD - Tia Irawan; Taufiqulloh Dahlan; Moh, Nurhadi; Novalia Nur Asysyfa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Based on the results of the 2023 Program for International Student Assessment (PISA) study, Indonesia is ranked 68th out of 72 countries. This research aims to determine the effect of the Problem Based Learning (PBL) learning model on students' critical thinking abilities. This research method uses a quasi-experimental method using pretest-posttest only control design. The population, namely all students from one of the elementary schools in Lembang sub-district, is 350 people. The population was continued with sample selection using a purposive sampling technique, 44 people were obtained, namely class IV A and IV B. Class IV A as the experimental class used the Problem Based Learning (PBL) learning model and class IVB used the conventional learning model (Jigsaw). Data was collected by giving tests, namely multiple choice, and non-tests, namely observation. The data analysis technique uses the Independent Simple T-Test, Effect Size and Normalized N-gain tests. Based on the research results, it was concluded that there is an influence between the Problem Based Learning (PBL) learning model on critical thinking skills.